2013
DOI: 10.1016/j.neuro.2013.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on methyl- and ethylmercury-induced toxicity in C6 glioma cells and the potential role of LAT-1 in mediating mercurial-thiol complexes uptake

Abstract: Various forms of mercury possess different rates of absorption, metabolism and excretion, and consequently, toxicity. Methylmercury (MeHg) is a highly neurotoxic organic mercurial. Human exposure is mostly due to ingestion of contaminated fish. Ethylmercury (EtHg), another organic mercury compound, has received significant toxicological attention due to its presence in thimerosal-containing vaccines. This study was designed to compare the toxicities induced by MeHg and EtHg, as well as by their complexes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 48 publications
3
42
0
1
Order By: Relevance
“…Consistent with these observations, the complex MeHg-S-Cys promoted a rise in Hg accumulation in brain and liver compared to MeHg-treated mice (Roos et al, 2010). In addition, a recent study showed that L-Met protects C6 rat glioma cell line from MeHg-S-Cys-induced toxicity, but not from MeHg (Zimmermann et al, 2013).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Consistent with these observations, the complex MeHg-S-Cys promoted a rise in Hg accumulation in brain and liver compared to MeHg-treated mice (Roos et al, 2010). In addition, a recent study showed that L-Met protects C6 rat glioma cell line from MeHg-S-Cys-induced toxicity, but not from MeHg (Zimmermann et al, 2013).…”
supporting
confidence: 64%
“…Based on these observations, as well as protective effects of L-Met against MeHg-S-Cys under in vitro conditions (Yin et al, 2008;Zimmermann et al, 2013) and on the fact that MeHg is found mostly bound to sulfhydryl-containing molecules such as cysteine in the environment (i.e., fish muscle), this study was undertaken to investigate the potential beneficial effects of L-Met against MeHg administered as MeHg-S-Cys-induced neurotoxicity in mice. Behavioral parameters related to the motor performance and biochemical parameters related to cerebellar antioxidant glutathione (GSH) system and Hg levels were evaluated in an attempt to elucidate potential mechanisms of neurotoxicity and neuroprotection.…”
mentioning
confidence: 99%
“…11,14,28 Until now, the involvement of the blood-CSF barrier in transfer of Hg compounds remains largely unexplored to our knowledge. In the present study we applied a well characterized cell culture model of the blood-CSF barrier derived from PCPECs 19 to investigate effects on and transfer across this important barrier in both directions (influx and efflux) after exposure to organic (MeHgCl and thiomersal) and inorganic (HgCl 2 ) mercury compounds for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…10 Recent in vitro based studies give evidence for a similar transfer mechanism by LAT1 for EtHg. 11 Speciation analysis in murine brain tissue provides evidence that EtHg can reach the brain after intramuscular injection of 20 mg thiomersal. 12 The observed presence of inorganic mercury in the brain tissue is likely to be due to a dealkylation of the organic Hg compounds as well as an oxidation of elemental mercury in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Thiomersal rapidly dissociates into ethyl-Hg chloride, ethyl-Hg hydroxide and sodium thiosalicylate in saline solutions, and the resulting ethyl-Hg species have high affinities for being bound to free thiols in living systems [9]. It is then actively transported across the blood brain barrier, including by the L-type neutral amino acid carrier transport (LAT) system, into human neuronal cells [10,11], where it significantly accumulates and persists for many months following exposure and alters numbers of neurons in the dentate gyrus of the hippocampus and thalamus [12,13].…”
Section: Forms Of Mercury Its Metabolism and Thiomersal Use In Vaccinesmentioning
confidence: 99%